People are unable to recognize or report on their own eye movements. Issue 11 (2nd November 2017) - Clarke, Alasdair D. F.; Mahon, Aoife; Irvine, Alex; Hunt, Amelia R.
ABSTRACT: Eye movements bring new information into our visual system. The selection of each fixation is the result of a complex interplay of image features, task goals, and biases in motor control and perception. To what extent are we aware of the selection of saccades and their consequences? Here we use a converging methods approach to answer this question in three diverse experiments. In Experiment 1, participants were directed to find a target in a scene by a verbal description of it. We then presented the path the eyes took together with those of another participant. Participants could only identify their own path when the comparison scanpath was searching for a different target. In Experiment 2, participants viewed a scene for three seconds and then named objects from the scene. When asked whether they had looked directly at a given object, participants' responses were primarily determined by whether or not the object had been named, and not by whether it had been fixated. In Experiment 3, participants executed saccades towards single targets and then viewed a replay of either the eye movement they had just executed or that of someone else. Participants were at chance to identify their own saccade, even when it contained under- and overshoot corrections. The consistent inability to report on one's own eye movements across experiments suggests that awareness of eye movements is extremely impoverished or altogether absent. This is surprising given that information about prior eye movements is clearly used during visual search, motor error correction, and learning.